Antimicrobial resistance pattern of cephalosporins in treatment of diabetic foot infection - T, Naresh; KV, Raghu; T, Prasad; NVRKT, Praveen; CK, Dhanapal; GP, Mohanta (Indian Journal of Pharmacy Practice)
Diabetes mellitus is a chronic disorder and affects large segment of population and is a major public health problem. Diabetic foot problems, such as ulcerations, infections and gangrene are the most common cause of hospitalization among diabetic patients. Although widely accepted as broad-spectrum antibiotics, cephalosporins are not active against all the bacteria commonly isolated in a hospital microbiological laboratory. Increasing prevalence of anti-microbial resistance is a major factor determining morbidity and mortality. The objective of the study is to study prescribing practice of cephalosporins, evaluate the sensitivity pattern of different generations of cephalosporins and to assess the treatment failure of cephalosporins in diabetic foot infections. A prospective study was done on 77 patients who fulfilled the inclusion criteria and had diabetic foot were included; prescribing pattern of cephalosporins and culture and sensitivity testing was studied for a period of 9 months. Retrospectively culture and sensitivity reports of 230 patients from last one year were screened. Cefotaxime was the most commonly prescribed antibiotic. Sensitivity pattern showed that 41.5% of gram-positive cocci were sensitive to cefotaxime, whereas 25% of gram-negative bacilli were sensitive. Gram-positive cocci were 29.3% resistant to Cefotaxime, whereas 57.1% of gram-negative bacilli were also resistant.Finally, organisms which were originally sensitive developed resistance approximately in a span of two weeks, probably due to antibiotic pressure. Treatment for longer duration may result in drug resistance. Finally, cefotaxime remains an active player in the treatment of diabetic foot infections, only when cautiously used resistance can be contained.
Keywords: Diabetic foot infections; Prescribing practices; Cephalosporins; Cefotaxime; Culture/sensitivity testing